The rice sector - Dorosh, Paul A.; Aung, Nilar; Minten, Bart (International Food Policy Research Institute, 2024)
Recent major local shocks have negatively affected Myanmar’s economy and its people. Disruptions in the world economy linked to the outbreak of COVID-19 in early 2020 and the Ukraine war in 2022 and 2023 have led to sharp price increases for petroleum products, wheat, vegetable oils, and other food products, as well as agricultural inputs, such as chemical fertilizers. Myanmar’s rice sector has also been adversely affected by increases in insecurity in rural areas, higher world prices, and reduced cross-border exports to China.